The Association Between Race/Ethnicity and Revision Following ACL Reconstruction in a Universally Insured Cohort. (4th September 2019) - Navarro, Ronald A.; Prentice, Heather A.; Inacio, Maria C.S.; Wyatt, Ronald; Maletis, Gregory B.
Abstract : Background: There have been few large studies involving multiethnic cohorts of patients treated with anterior cruciate ligament reconstruction (ACLR), and therefore, little is known about the role that race/ethnicity may play in the differential risk of undergoing revision surgery following primary ACLR. The purpose of this study was to evaluate whether differences exist by race/ethnicity in the risk of undergoing the elective procedure of aseptic revision in a universally insured cohort of patients who had undergone ACLR. Methods: This was a retrospective cohort study conducted using our integrated health-care system's ACLR registry and including primary ACLRs from 2008 to 2015. Race/ethnicity was categorized into the following 4 groups: non-Hispanic white, black, Hispanic, and Asian. Multivariable Cox proportional-hazard models were used to evaluate the association between race/ethnicity and revision risk while adjusting for age, sex, highest educational attainment, annual household income, graft type, and geographic region in which the ACLR was performed. Results: Of the 27, 258 included patients, 13, 567 (49.8%) were white, 7, 713 (28.3%) were Hispanic, 3, 725 (13.7%) were Asian, and 2, 253 (8.3%) were black. Asian patients (hazard ratio [HR] = 0.72; 95% confidence interval [CI] = 0.57 to 0.90) and Hispanic patients (HR = 0.83; 95% CI = 0.70 to 0.98) had a lower risk of undergoing revision surgery than did white patients. Within the first 3.5 years postoperatively, we did not observe a difference in revision risk when black patients were compared with white patients (HR = 0.86; 95% CI = 0.64 to 1.14); after 3.5 years postoperatively, black patients had a lower risk of undergoing revision (HR = 0.23; 95% CI = 0.08 to 0.63). Conclusions: In a large, universally insured ACLR cohort with equal access to care, we observed Asian, Hispanic, and black patients to have a similar or lower risk of undergoing elective revision compared with white patients. These findings emphasize the need for additional investigation into barriers to equal access to care. Because of the sensitivity and complexity of race/ethnicity with surgical outcomes, continued assessment into the reasons for the differences observed, as well as any differences in other clinical outcomes, is warranted. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.